Treatment of severe pediatric atopic dermatitis with methotrexate: A retrospective review. Issue 3 (27th February 2019) - Anderson, Kathryn; Putterman, Elana; Rogers, Rachel S.; Patel, Deepa; Treat, James R.; Castelo‐Soccio, Leslie
Abstract : Abstract: Background/Objectives: Severe atopic dermatitis (AD) may require systemic immunomodulatory agents to control symptoms. A lack of evidence and guidelines for systemic AD therapy in children has led to variability in agents selected and uncertainty in their comparative efficacy and safety. Evaluation of the efficacy of methotrexate in children with severe AD was performed. Methods: We performed a retrospective chart review of 55 pediatric patients seen at Children's Hospital of Philadelphia that measured improvement using the Investigator's Global Assessment (IGA), a scale that rates AD symptoms from 0 to 5. Results: About 76% of patients showed improvement with methotrexate. Mean baseline IGA of all patients was 4.18. After 6‐9 months of treatment, this improved to 2.94. There was additional improvement to a mean IGA score of 2.39 after 12‐15 months of treatment. At the final visit before each patient stopped methotrexate, the mean IGA score was 2.71. Approximately 50% of patients experienced minor side effects with gastrointestinal side effects the most common. Conclusions: In a diverse patient population, safety and efficacy of methotrexate was demonstrated. Significant improvement in IGA was noted for the majority after 6‐9 months of therapy with further improvement when continuing treatment to 12‐15 months. Methotrexate remains an important option for long‐term symptom control with a favorable side effect profile and low cost.